Особливості оцінювання енергоекологічного ефекту від впровадження термомодернізації в міських теплових мережах - Яковишина, Т. Ф. (My University, 2023)
Мета. Аналіз особливостей практичного застосування відомих методів визначення енергетичних і екологічних показників котелень в системах теплових мережах міста «до» та «після» впровадження термомодернізації житлових будинків. Методика дослідження передбачає критичний аналіз існуючої методики визначення викидів в атмосферу з енергетичних установок та рекомендації стосовно визначення енергетичної й екологічної ефективності термомодернізацї будинків. Результати дослідження. Аналіз стандартизованої методики розрахункового визначення викидів забруднюючих речовин в атмосферу з енергетичних установок, включаючи міські котельні, показав необхідність її удосконалення за рахунок виокремлення із розрахованих показників витрат палива і викидів частки, що обумовлена впровадженою термомодернізацією. Рекомендовано доповнити указану методику розрахунком «енергоекологічного індексу» (К), запропонованого у 2020 році. Особливістю застосування цього індексу в умовах котельні, де відбулася будь яка термомодернізація, потрібно обрати поточні витрати палива «до» і «після» її впровадження, але визначені при однаковій атмосферній температурі, наприклад 0оС, та відповідно розрахувати пару значень індексу. Різниця між ними дозволить оцінити спочатку величину збереження (економії) палива, тобто енергетичний ефект термомодернізації, а потім розрахувати різницю відповідних поточних пар значень викидів кожної забруднюючої речовини, як екологічний ефект термомодернізації. Наукова новизна полягає в рекомендації удосконалення стандартизованої методики за рахунок виокремлення із визначених за нею витрат палива і викидів частки, що обумовлена впровадженою термомодернізацією, на основі використання відомого енергоекологічного індексу, для розрахунків якого потрібно обрати поточні витрати палива «до» і «після» термомодернізації, але визначені при однаковій атмосферній температурі. Практичне значення. Отримані розрахункові показники пропонуються використовувати для визначення енергетичної й екологічної ефективності термомодернізацї в системі певної котельні, включаючи будинки як чинників екологічної безпеки територій міста.

Purpose. Analysis of the features of the practical application of well-known methods for determining the energy and environmental indicators of boiler houses in the systems of heating networks of the city "before" and "after" the introduction of thermal modernization of residential buildings network. The methods. provides for a critical analysis of the existing methodology for determining emissions into the atmosphere from power plants and recommendations for determining the energy and environmental efficiency of thermal modernization of buildingsimplementation of thermal modernization of residential buildings network. Findings. The analysis of the standardized methodology for calculating emissions of pollutants into the atmosphere from power plants, including urban boiler houses, showed the need for its improvement by separating from the calculated indicators of fuel consumption and emissions the share due to the implemented thermal modernization. It is recommended to supplement this methodology with the calculation of the "energy ecological index" (K) proposed in 2020. The peculiarity of the application of this index in the conditions of the boiler house, where any thermal modernization has taken place, is to select the current fuel consumption "before" and "after" its implementation, but determined at the same atmospheric temperature, for example, 0 °C, and accordingly calculate a pair of index values. The difference between them will allow you to first estimate the value of fuel conservation (savings), i.e. the energy effect of thermal modernization, and then calculate the difference between the corresponding current pairs of emission values of each pollutant, as the environmental effect of thermal modernization. The originality consists in recommending the improvement of the standardized methodology by allocating from the determined fuel consumption and emissions the share due to the implemented thermal modernization, based on the use of a well-known energy ecological index, for the calculation of which it is necessary to select the current fuel consumption "before" and "after" thermal modernization, but determined at the same atmospheric temperature. Practical implementation. The obtained calculated indicators are proposed to be used to determine the energy and environmental efficiency of thermal modernization in the system of a certain boiler house, including buildings as factors of environmental safety of the city territories.
Features of evaluation of the energy-ecological effect from the introduction of thermal modernization in urban heating networks
Keywords: термомодернізації будівель; методи визначення викидів забруднюючих речовин котельнями; енергетична та екологічна ефективність термомодернізації; thermal modernization of buildings; methods for determining emissions of pollutants by boiler houses; energy and environmental efficiency of thermal modernization